Mechanical behaviour of high strength concrete modified with triple blend of fly ash, silica fume and steel fibers. (2022) - Kumar, Mavoori Hitesh; Saikrishnamacharyulu, Ippilli; Mohanta, Nihar Ranjan; Ashutosh, Anikam; Mishra, Prajnananda; Samantaray, Sandeep
Abstract: Mechanical strength is the prominent property of concrete which is solely responsible for the long and excellent structural performance of the concrete structures under extreme adverse environmental conditions. Core strength of the concrete mainly the compressive strength is the key factor that contributes long term load performance against adverse climatic conditions and serviceability to the structures and the enhancement of these properties is indirectly associated with the significant improvement of other properties of concrete such as porosity, water absorption, permeability properties etc. It is mainly aimed to study the contribution of triple blend of fly ash, silica fume and steel fibers in the enhancement of mechanical strength of concrete. Concrete mixes were prepared by utilizing fly ash (FA) as 0%, 15% & 30% replacement levels which are coupled with silica fume (SF) in varying percentages of 0%, 6%, 12% & 18% by mass substitutions of cement along with three varying amounts of steel fibers i.e. 0%, 0.5%, 1% by volume of concrete. All concrete mix proportions were tested to investigate the enhancement in the strength behaviour of concrete subjected to a curing duration of 28 days. Results reported that an optimum mix of 15% FA, 12% SF and 1% inclusion of steel fibers achieved higher compressive strength by 5.89% rise with improved workability results and showed a remarkable performance in terms of flexural and split tensile strength with an increment of 20.40% and 28.02% respectively. Hence, it is confirmed that the triple blending mix of FA, SF and steel fibers can be adopted to achieve significant improvement in terms of strength and workability of concrete.